2007
DOI: 10.1677/jme-06-0040
|View full text |Cite
|
Sign up to set email alerts
|

Association of estrogen receptor   with plasma-membrane caveola components: implication in control of vitamin D receptor

Abstract: This study was designed to provide a direct demonstration of the importance of caveolin-1 in the compartmentalization of estrogen receptor b (ERb) to the membrane, thus allowing 7b-estradiol (E2) to control vitamin D receptor (VDR) transcription and expression. Our strategy was to obtain cell lines expressing different levels of caveolin-1. To this end, we transfected human embryonic kidney 293 cells with a caveolin-1-expressing vector and obtained three cell-line variants: one expressing high amounts of caveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 61 publications
0
15
1
Order By: Relevance
“…Therefore, when 25(OH)D level is low, a genetic component does not contribute further to variation among individual adolescent females as it does among males. It is also possible that there are strong gender-specific hormonal effects that regulate 25(OH)D levels, such as in one animal study where estradiol up-regulated the expression of vitamin D receptors (36). Further studies are needed to examine these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when 25(OH)D level is low, a genetic component does not contribute further to variation among individual adolescent females as it does among males. It is also possible that there are strong gender-specific hormonal effects that regulate 25(OH)D levels, such as in one animal study where estradiol up-regulated the expression of vitamin D receptors (36). Further studies are needed to examine these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the regulation of growth plate chondrocytes by 1␣,25(OH) 2 D 3 requires caveolae and cav-1 [4]. Recently it was reported the key role of cav-1 in the compartmentalization of estrogen receptor ␤ (ER␤) to the plasma membrane, thus allowing estradiol to control VDR transcription and expression [20]. In view of the data described, our aim was to investigate the role of caveolae and cav-1 in 1␣,25(OH) 2 D 3 -dependent modulation of kinase cascades and VDR localization in skeletal muscle cells.…”
Section: Introductionmentioning
confidence: 99%
“…In platelets, Tan IIA modulates APP metabolism possibly via membrane ER-mediated nongenomic signaling. It was demonstrated that membrane ERs reside in the lipid rafts (15,16), where the ER isoform, ERα, activates PI3K through membrane recruitment and direct interaction with PI3K (17). ERα binds in a ligand-dependent manner to the p85α regulatory subunit of PI3K, leading to the phosphorylation of Akt (18).…”
Section: Discussionmentioning
confidence: 99%